Graphene: Ultra‐Efficient Photocatalytic Properties in Porous Tungsten Oxide/Graphene Film under Visible Light Irradiation (Adv. Sci. 12/2015). Issue 12 (December 2015) - Mei, Lin; Zhao, Haitao; Lu, Bingan
Abstract : In article 1500116, B. Lu and co‐workers successfully demonstrate the production of a high performance, highly porous WO3 nanoframework with graphene film photocatalyst via an electrospinning method. The plentiful exposed graphene nanosheets can great adsorb RhB molecules via π–π stacking and reduce the recombination rate of electrons and holes.